Role of technology in future teachers’ training: Case study of ESEFA students, Morocco - JAMYLY, Sana EL; ABAKARIM, Ismahane (Edelweiss Applied Science and Technology, 2025)
This study explores how technology adoption influences the professional development of future teachers at ESEF Agadir, Morocco, examining determinants of technology use within the UTAUT model framework. A qualitative methodology was employed through semi-structured interviews with 32 students from all disciplines (Mathematics, Sciences, French, English, Amazigh, and Primary Education) and study levels. Interviews were analyzed using NVIVO software, combining lexical and thematic analysis within an inductive and constructivist epistemological stance. The analysis reveals that UTAUT determinants—perceived usefulness, perceived effort, social influence, and facilitating conditions—remain central to the intention and actual use of digital technology. However, four contextual dimensions emerge as equally decisive: pedagogical creativity, identity engagement, structural inequalities in resource access, and peer solidarity, significantly shaping the technology appropriation process. While the UTAUT model proves robust in explaining technology adoption, emerging contextual variables highlight the necessity of adapting it to local realities. Technology integration in teacher training cannot be understood solely through universal determinants but must account for cultural, material, and social specificities. These findings underscore the importance of developing teacher training programs that integrate local specificities, promote collaborative learning, address structural inequalities, and leverage pedagogical creativity to optimize support and teacher professionalization in Moroccan educational contexts.